2009
DOI: 10.1515/znb-2009-0418
|View full text |Cite
|
Sign up to set email alerts
|

A New Lanostane Triterpene from Skimmia laureola

Abstract: Aerial parts of Skimmia laureola yielded a new (+)-lanostane-3β ,24-dihydroxy-25-ene triterpene (1) along with fourteen known compounds. The structures were identified by spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It was investigated in previous report by AAS that decrased in concentration of silver ions in reaction mixture as time proceeded indicated the conversion of Ag ions to silver nanoparticles [19]. FTIR results are strongly supported by the previous investigation on the chemical constituent of the leaves of S. laureola [20,21] and it was suggested that water soluble compounds such as flavonoids, terpenoids are responsible for capping and efficient stabilization of nanoparticles, as they have the ability to cap silver nanoparticles and stabilized them at definite size and shape [22]. The recent study on S. laureola mediated AgNPs showed that premier antibacterial potential as compared to previous reported study on antibacterial activity of silver nanoparticles synthesized from stem extract of Svensonia hyderobadensis was evaluated at a 10 μg ml À 1 against human pathogens [23].…”
Section: Discussionsupporting
confidence: 69%
“…It was investigated in previous report by AAS that decrased in concentration of silver ions in reaction mixture as time proceeded indicated the conversion of Ag ions to silver nanoparticles [19]. FTIR results are strongly supported by the previous investigation on the chemical constituent of the leaves of S. laureola [20,21] and it was suggested that water soluble compounds such as flavonoids, terpenoids are responsible for capping and efficient stabilization of nanoparticles, as they have the ability to cap silver nanoparticles and stabilized them at definite size and shape [22]. The recent study on S. laureola mediated AgNPs showed that premier antibacterial potential as compared to previous reported study on antibacterial activity of silver nanoparticles synthesized from stem extract of Svensonia hyderobadensis was evaluated at a 10 μg ml À 1 against human pathogens [23].…”
Section: Discussionsupporting
confidence: 69%
“…Effect of various concentrations of 2 on acetylcholinesterase inhibition. Natural Product Research 309 lipoxygenase and cholinesterase activity (Atta-ur-Rahman et al, 2006;Sultana et al, 2008). The crude petroleum ether extract of R. stricta exhibited lipoxygenase activity(Sultana et al, 2005a) with 42.98% inhibition at a concentration of 40 mg 200 mL À1…”
mentioning
confidence: 99%
“…Seeds of S. laureola were shown to be a rich source of polyunsaturated fatty acids: the apolar extract, analyzed by GC-MS after derivatization as methyl esters, afforded the following percentages of the respective acids: palmitic 8.28%, stearic 1.47%, palmitoleic 2.57%, oleic 33.41%, linoleic 31.15%, and linolenic 23.12% (Pasha et al, 1966). Skimmidiol fatty acid ester 104 was isolated from aerial parts (Sultana et al, 2005) and the similar compound skimmilaureol 103 was isolated from leaf extracts by Sultana et al (2008).…”
Section: S Laureolamentioning
confidence: 99%
“…Compound 3 also showed a dose-dependent spasmolytic effect mediated through Ca 2+ channel blocking in an isolated rabbit jejunum intestinal preparation (Atta-ur-Rahman et al, 2006). Two different compounds, O-methyl-cyclolaudenol triterpene 74 and 7-methoxy-6-(3 0 -hydroxy-2 0 R-methoxy-3 0 -methyl butyl)-coumarin 28, exerted inhibitory activity against prolyl endopeptidase with IC 50 values of 8.2 and 39.6 lM, respectively (Sultana et al, 2008). Skimmidiol fatty ester 104 showed in vitro tyrosinase activity with an IC 50 of 51.2 lM; a value, which is three and fourteen times lower than the ones measured for the positive controls, kojic acid and L-mimosine, respectively (Sultana et al, 2005).…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%